Penerapan Algoritma C4.5 Untuk Penerimaan Siswa Baru Pada SMA Al-Azhar Medan - Hts, Dedek Indra Gunawan (STIKOM Tunas Bangsa Pematangsiantar, 2018)
Schools with good reputation are very concerned about the admission selection process. Al-Azhar Medan High School is very concerned about this admission process. Every year many parents register their children to enter Al-Azhar High School Medan. Besides having good school facilities the teachers also have good competencies. The number of students who register makes the selection process take a long time. The C4.5 algorithm is one algorithm that changes the fact that is quite large into a decision tree. This algorithm is expected to be able to solve problems that occur in Al-Azhar High School Medan.